The influence of responsible leadership on organizational commitment: the mediating role of trust in leaders in the higher education sector - Afzal, Muhammad; Soroya, Saira; Chaudhary, Naveed; Niazi, Abdul; Ashiq, Murtaza (RADS Journal of Business Management, 2025)
Background: This study examines the impact of responsible leadership (RL) on organizational commitment by examining the mediating role of trust in the leader, as modeled by the four key dimensions of the leader's role (aggregate of virtues, principles and ethical values, stakeholder involvement, and model of the leader's role) in the context of social identity theory. Methods: We employed a quantitative research design, surveying 300 middle-level employees in grades 11 to 16 from the University of the Punjab, Lahore, Pakistan. Data collection involved a structured questionnaire covering key leadership and trust dimensions. The data analysis utilized SPSS version 22 and ADANCO version 2.2, with structural equation modeling to test hypotheses. Results: Results show that organizational commitment is significantly influenced by stakeholder involvement (0.03 p-value) and ethical principles (0.00 p-value). The aggregate of virtues (0.79 p-value) and leadership role modeling (0.26 p-value) have an insignificant direct impact. However, trust significantly mediates the relationship between organizational commitment and stakeholder involvement (0.01 p-value). Trust’s mediation effect on the link between ethical principles and organizational commitment is minimal (0.04 p-value). Conclusion: This study suggests that implementing RL practices, particularly in stakeholder involvement and ethical leadership, enhances employee commitment. Responsible leadership cultivates a positive corporate image, attracting committed stakeholders. To maximize benefits, organizations should provide senior leaders with behavioral training in RL practices, fostering an environment that boosts employee loyalty. Leadership development programs should include modules on ethical decision-making, stakeholder communication, and trust-building strategies.
Keywords: Context (archaeology); Ethical leadership; Mediation; Organizational commitment; Stakeholder; Stakeholder engagement; Stakeholder theory; Structural equation modeling; dept.ils

Mental Health Needs of Families of Patients in Intensive Care Units and the Role of Mobile Health: Survey Study - Faiola, Anthony; Soroya, Saira; Hao, Zhonglin; Munker, Reinhold (JMIR Formative Research, 2025)
BACKGROUND: The experiences of patients with COVID-19 and their families manifested the most devastating effects of family separation since the 1918 Spanish influenza pandemic and, with it, a call for solutions to patient isolation and its effect on family mental health. OBJECTIVE: This study examined the recent experiences of families of critical care (intensive care unit; ICU) patients related to anxiety and depression (AD), satisfaction with clinician-family communication, and counseling from mental health and social services. This study explored correlations between these factors and family interest in mobile health (mHealth) designed to improve information flow and communication from patient bedside to remote families. METHODS: Using a 36-question quantitative survey, we collected 97 responses over 6 months. We selected participants by using a convenience sampling strategy. To analyze data, we applied descriptive and inferential statistics. Participants represented a spectrum of ages, relationships to patients, and races (n=78, 80% White; n=17, 18% Black; n=2, 2% other races). Approximately 17% (n=16) of the patients were admitted for cancer, 13% (n=13) were admitted for COVID-19, and 21% (n=20) were admitted for other conditions. RESULTS: The mean score for remote families' satisfaction with patient health updates from the bedside and mental health services was 2.94 (SD 1.31), whereas that for phone communication was lower on average. The mean scores of family AD levels were elevated, and levels were higher among family members during the ICU stay than after discharge. These findings confirmed evidence of a negative correlation between transportation difficulties and satisfaction with the frequency of information provided (r=-0.284; P=.005), suggesting that, with the increase in transportation challenges, families become less satisfied with the frequency of patient health information. Family members expressed strong interest in using mHealth information and communication services (mean 8.34, SD 1.98) and having easy access to social workers to manage AD (mean 8.29, SD 2.03). Families experiencing higher levels of anxiety during patients' ICU stays had significantly greater interest in the use of an mHealth app that would provide direct access to social workers (r=0.326; P<.001), in using an mHealth videoconferencing app (r=0.319; P=.002), and in overall mHealth app use (r=0.322; P<.001). CONCLUSIONS: Family members experienced high levels of AD during patient ICU admission, as well as after discharge even though their mental health challenges were reduced. Families were highly dissatisfied with the frequency of health updates, with lower satisfaction reported among those who faced difficulties arranging transportation or lived further from the hospital. Modest but statistically significant correlations were observed between family members' reported mental health status during ICU stays and an interest in an mHealth app that could provide access to real-time bedside information, facilitate communication with bedside nurses, and support connections with social workers.
Keywords: Affect (linguistics); COVID-19; Depression (economics); Health care; ICU; Mental health; Mental illness; Receipt; communication; dept.ils; digital tools; eHealth; health equity; health technology; intensive care unit; mental health; mobile health

Advancing Library Services for Mobile Users - Liu, Yan Quan (IGI Global Scientific Publishing, 2025)
As mobile technology becomes integral to everyday life, libraries rework their services to meet the needs of their users. Advancing library services for mobile users requires seamless, intuitive experiences that support research, learning, and engagement. From mobile-friendly catalogs and e-book pla...
Publication Title: https://services.igi-global.com/resolvedoi/resolve.aspx?doi=10.4018/978-1-7998-9175-8
Keywords: dept.ils

A Study of the Coverage of Open Educational Resources (OER) Through Websites of Colleges and Universities in Connecticut - Brown, Mary; Kim, Hak Joon (Practical Academic Librarianship: The International Journal of the SLA Academic Division, 2025)
Notwithstanding reports of increased awareness and use of Open Educational Resources (OER) in higher education, the literature notes that awareness and use of and institutional support for OER remain major challenges to campuses seeking to reduce student cost burden and support access to materials. OER also support faculty who desire to move beyond the traditional textbooks in order to increase their students’ engagement and thereby access to learning, to support pedagogical changes they are making that enhance student learning, and to give faculty greater control over their courses. The university website, as a public-facing vehicle to aid students, parents, alumni, faculty, the community, and interested others in being aware, among other things, of the resources available, is examined for findable support for OER. The purpose of this study is to show, through examination of their websites, a snapshot of the response of Connecticut universities and colleges to OER. Through an examination of these websites, we gage the ability to connect with information related to OER through the university website.
Keywords: dept.ils

Artificial Intelligence, Misinformation, and Libraries: A New Frontier for Information Professionals - Salubi, Oghenere (Proceedings of the Association for Information Science and Technology, 2025)
Generative artificial intelligence (AI) has experienced rapid advancement, fundamentally transforming the information landscape. This technological shift has not only amplified the dissemination of misinformation but has also posed significant challenges to conventional frameworks of trust and verification. This paper explores the dual impact of AI: its potential to enhance information services while simultaneously amplifying misinformation and disinformation. Seven AI-generated misinformation cases between 2022 and 2025—ranging from deepfakes and political propaganda to impersonation and amplification were analyzed. Through thematic case analysis and interdisciplinary synthesis, the study proposes the AI-Misinformation Resilience Model (AIM-RM), a conceptual framework guiding proactive responses across verification infrastructure, digital literacy, and ethical policy engagement. Drawing on recent scholarly literature and grounded in information ethics, epistemic trust, and sociocultural literacy, the model offers a path forward for LIS professionals seeking to navigate the post-truth era. Annual Meeting of the Association for Information Science & Technology | Nov. 14 – 18, 2025 | Washington, DC, USA.
Keywords: Deepfakes; Generative artificial intelligence; Information literacy; Library and information professionals; Misinformation; dept.ils

Developing a Video Game Metadata Schema and Fillable Form Template for Accessible Interactive Media Cataloging in Public Libraries - Myers, Jason (Cataloging & Classification Quarterly, 2025)
Keywords: Cataloging; Computer science; Information retrieval; Metadata; Multimedia; Schema (genetic algorithms); Video game; World Wide Web; cataloging interactive media; dept.ils; fillable forms; metadata schema; public libraries; video games

Adopting Critical Cataloging Practices Post Diversity Audit: Connecting the Community to Your Collection - Anderson, Jessica K.; Liu, Yan Quan (Library Resources & Technical Services, 2025)
To increase patrons’ ability to find resources, it is imperative to investigate barriers and biases in thedescriptive catalog data for inclusive collection management and development standards. This studyused a specially designed descriptive approach to gather quantitative data from 101 public librariansin Connecticut via a Qualtrics survey to identify the key variables that influence the successfulenhancement of online public access catalog (OPAC) metadata after a diversity audit of the librarymaterials. The results revealed factors that promote or impede the integration of inclusive catalogingthat reflects the diversity of the community: (1) appreciating the benefits of audit methods that arefocused on bibliographic records, (2) recognizing the need for buy-in and participation from theentire organization, and (3) stressing the useful integration of institutional and community feedbackto improve the collection’s accessibility and representation. The findings provide practical adviceto public libraries that want to satisfy the diverse demands of their user base by integrating criticalcataloging frameworks into their diversity and inclusion objectives.
Keywords: SCSU-student; dept.ils

Digitization Practices in U.S. Urban Libraries: Tools, Technologies, and Metadata Standards - Torres, Natalia; Liu, Yan (Public Library Quarterly, 2025)
Keywords: Business; Computer science; Cultural heritage preservation; Data science; Digitization; Engineering; Library science; Metadata; SCSU-student; Telecommunications; World Wide Web; dept.ils; digital collections; digitization practices; online accessibility; urban libraries

Integrating tacit knowledge transfer model in academic context: a sem analysis approach - Shahzad, I.; Soroya, S.H. (Journal of the Knowledge Economy, 2025)
Tacit knowledge is more precious as compared to explicit, as it is the intellectual property of the knower and resides in one’s mind. A major part of our knowledge is tacit, which is either lost or not recorded/ captured. In the late 1950s, the term “tacit knowledge” appeared in the literature and received the attention of the researchers. However, a majority of the studies pertaining to tacit knowledge (TK) have primarily focused on non-educational contexts, despite the fact that pragmatic knowledge holds paramount importance within academic settings. This study is designed to examine the tacit knowledge process from capturing to sharing in an academic setting. A cross-sectional questionnaire-based survey research method was adopted to conduct this research, and data was collected through a well-structured questionnaire. Postgraduate students at the University of the Punjab, Lahore, Pakistan, were the study population. The findings revealed that cognitive skills enable and motivate individuals to capture tacit knowledge, and the positive capturing behavior leads to better handling and more sharing of tacit knowledge, whereas technical skills enable them to better handle tacit knowledge, which ultimately leads to wise utilization of tacit knowledge, and social skills help them in capturing, keeping, and use of tacit knowledge. The study argues that tacit knowledge flow is depending on a certain set of skills and behavior. The findings of the study will be supportive of higher academic institutions as they are the powerhouse of knowledge creation. © This is a U.S. Government work and not under copyright protection in the US; foreign copyright protection may apply 2024.
Keywords: Higher education; Implicit knowledge; Knowledge management; Social behaviors; dept.ils; peer-reviewed

Perceived awareness, benefits, and strategies of Pakistani editors regarding open-access journal publishing - Raza, Muhammad Zahid; Rafiq, Muhammad; Soroya, Saira Hanif (Global Knowledge, Memory and Communication, 2025)
This study aims to discover the perceived awareness, benefits and suitable strategies of the Pakistani editors of Higher Education Commission (HEC)-recognized scholarly journals regarding open-access (OA) journal publishing in Pakistan.,A structured questionnaire-based survey method of quantitative research approach was adopted to achieve the study’s objectives by collecting data from the editors of 329 HEC-recognized journals in Pakistan.,The awareness level of the respondents of the Pakistani journals is low regarding the OA concepts, resources and initiatives. The respondents of OA journals have better awareness levels than the respondents of non-OA journals. All the respondents of journals are convinced and have the view that OA journals have wider benefits for the academic community, and they need to flourish. A majority of the respondents are of the view that HEC should sponsor financial resources and technical training for OA journal publishing. The respondents of OA journals are more in favor of supporting OA journal publishing than the respondents of non-OA journals.,This study covered the lists of HEC-recognized journals of 2019. More studies may be conducted based on updated lists of HEC-recognized journals by using different research paradigms such as qualitative or pragmatic research approaches.,To the best of the authors’ knowledge, this study is the first comprehensive study on this phenomenon and is an effort to fill this gap and invigorate the scholarly literature. It may attract the attention of the policymakers, funding bodies, parent institutions of the journals and the HEC to cope with the low awareness level of the Pakistani editors regarding the OA concepts, resources and initiatives; and suitable strategies required to uplift the OA journal publishing paradigm in Pakistan.
Keywords: dept.ils; peer-reviewed

Perceptions of the Pakistani editors for open access journal publishing: a developing country’s perspective - Raza, Muhammad; Rafiq, Muhammad; Soroya, Saira (Information Development, 2025)
Objectives This study has been designed to determine Pakistani editors’ perceptions regarding the Open Access (OA) publishing practices of the Higher Education Commission (HEC)-recognized journals in Pakistan, and to assess their best OA publishing models. Methodology A structured questionnaire-based survey method of quantitative research approach was adopted to achieve the study’s objectives by collecting data from the editors of all 329 HEC-recognized journals in Pakistan. Findings This study exposed that public and teaching institutes are leading in OA journal publishing in Pakistan as compared to private and research institutes. Diamond OA, and Gold OA publishing models are popular among the respondents; however, respondents are not convinced to follow any specific OA publishing model due to their different choices. A large majority (92%) of the journals belong to the Y category (the lowest) of journals. A large majority (72%) of the journals in Pakistan is adopting the Open Journal System (OJS), and parent institutions installed web browsers. CC-BY-NC and CC-BY licenses are their favorite licenses. Significance The present study is the first comprehensive study on editors’ perceptions for OA journal publishing and is an effort to fill this gap to invigorate the scholarly literature. This study may enable the journals, editors, and publishers to follow the best OA journal publishing practices of the Pakistani journals for global OA usage of scholarly journals. The results have practical and theoretical ramifications for academic and research institutions, federal and provincial higher education commissioners, policy organizations, and parent institutions of journals.
Keywords: Computer science; Developing country; Economic growth; Economics; Library science; MEDLINE; Media studies; Open access journal; Open access publishing; Perception; Perspective (graphical); Political science; Psychology; Public relations; Publishing; Scopus; Sociology; dept.ils; peer-reviewed